Five-Year Clinical Outcomes of Local versus General Anesthesia Deep Brain Stimulation for Parkinson’s Disease - Sheng-Tzung Tsai; Tsung-Ying Chen; Sheng-Huang Lin; Shin-Yuan Chen (Parkinson's Disease)
Background. Studies comparing long-term outcomes between general anesthesia (GA) and local anesthesia (LA) for STN-DBS in Parkinson’s disease (PD) are lacking. Whether patients who received STN-DBS in GA could get the same benefit without compromising electrophysiological recording is debated. Methods. We compared five-year outcomes for different anesthetic methods (GA vs LA) during STN-DBS for PD. Thirty-six consecutive PD patients with similar preoperative characteristics, including age, disease duration, and severity, underwent the same surgical procedures except the GA (n=22) group with inhalational anesthesia and LA (n=14) with local anesthesia during microelectrode recording and intraoperative macrostimulation test. Surgical outcome evaluations included Unified Parkinson’s Disease Rating Scale (UPDRS), Mini-Mental Status Examinations, and the Beck Depression Inventory. Stimulation parameters and coordinates of STN targeting were also collected. Results. Both groups attained similar benefits in UPDRS part III from STN-DBS (GA 43.2 ± 14.1% vs. LA 46.8 ± 13.8% decrease, p=0.45; DBS on/Med off vs. DBS off/Med off) and no difference in reduction of levodopa equivalent doses (GA 47.56 ± 18.98% vs. LA 51.37 ± 31.73%, p=0.51) at the five-year follow-up. In terms of amplitude, frequency, and pulse width, the stimulation parameters used for DBS were comparable, and the coordinates of preoperative targeting and postoperative electrode tip were similar between two groups. There was no difference in STN recording length as well. Significantly less number of MER tracts in GA was found (p=0.04). Adverse effects were similar in both groups. Conclusions. Our study confirmed that STN localization with microelectrode recording and patient comfort could be achieved based on equal effectiveness and safety of STN-DBS under GA compared with LA.